INTERNALISASI NILAI-NILAI KARAKTER RELIGIUS SISWA DI MADRASAH IBTIDAIYYAH NURUSSALAM MANTINGAN - Rini Setyaningsih; Siti Nikmatul Rochma (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
This study aims to determine the madrasah strategy in internalizing the values of religious character to students. The type of research the writer uses is descriptive qualitative research, with data collection techniques using in-depth interviews, documentation and participatory observation. Data analysis techniques in this study used data reduction, data presentation and data verification. The internalization stage or inculcation of religious character values for classes 1-2 MI Nurussalam is at the value transformation stage, classes 2 (process) and 3 are at the value transaction stage, while classes 4, 5 and 6 MI are at the value trans-internalization stage. MI Nurussalam's strategy in internalizing the values of religious character is divided into two fields, namely the academic and non-academic fields. The strategy in the academic field of MI Nuruusalam is to develop the Madrasah curriculum from grade 1 to grade 6 by adding special Islamic subjects and fostering a love affair with Arabic (the key to opening Islamic insights). In the non-academic field, MI Nurussalam integrates religious character values into routine activities, spontaneous activities, exemplary activities, and the Madrasah environmental conditioning system.